2018
DOI: 10.1016/j.pscychresns.2018.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic and benzodiazepine use and brain morphology in schizophrenia and affective psychoses – Systematic reviews and birth cohort study

Abstract: The aim of this paper was to investigate differences in brain structure volumes between schizophrenia and affective psychoses, and whether cumulative lifetime antipsychotic or benzodiazepine doses relate to brain morphology in these groups. We conducted two systematic reviews on the topic and investigated 44 schizophrenia cases and 19 with affective psychoses from the Northern Finland Birth Cohort 1966. The association between lifetime antipsychotic and benzodiazepine dose and brain MRI scans at the age of 43 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 84 publications
0
1
0
Order By: Relevance
“…In comparison to amyloid reduction, the effect of BZDs on hippocampal volume has been less studied. One clinical study found an independent positive association of BZD use and hippocampal volume in a population of middle-aged psychiatric patients 35 . Preclinical studies show inconsistent findings on the effect of BZDs on BDNF in the hippocampus of mice, such that acute but not repeated BZD treatment decrease BDNF concentration 36 .…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to amyloid reduction, the effect of BZDs on hippocampal volume has been less studied. One clinical study found an independent positive association of BZD use and hippocampal volume in a population of middle-aged psychiatric patients 35 . Preclinical studies show inconsistent findings on the effect of BZDs on BDNF in the hippocampus of mice, such that acute but not repeated BZD treatment decrease BDNF concentration 36 .…”
Section: Discussionmentioning
confidence: 99%